2023
DOI: 10.1038/s41598-023-35925-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of plasma circulating tumor DNA in patients with heavily pretreated HER2 + metastatic breast cancer

Abstract: We explored accumulated genomic alterations in patients with heavily treated HER2 + metastatic breast cancer enrolled in the KCSG BR18-14/KM10B trial. Targeted sequencing was performed with circulating tumor DNAs (ctDNAs) collected before the treatment of 92 patients. ctDNAs collected at the time of disease progression from seven patients who had a durable response for > 12 months were also analyzed. Sixty-five genes were identified as pathogenic alterations in 99 samples. The most frequently altered genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Multi-omics mutation analysis based on the CRRS model can identify specific genomic changes related to the circadian rhythm of BC, and could lead to more precise and individualized therapeutic strategies for patients with BC. Previous research has shown that somatic mutations are associated with poor outcomes in BC [ [53] , [54] , [55] , [56] ]. We investigated the differences in the distribution of somatic mutations between populations at different risk levels.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-omics mutation analysis based on the CRRS model can identify specific genomic changes related to the circadian rhythm of BC, and could lead to more precise and individualized therapeutic strategies for patients with BC. Previous research has shown that somatic mutations are associated with poor outcomes in BC [ [53] , [54] , [55] , [56] ]. We investigated the differences in the distribution of somatic mutations between populations at different risk levels.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, ERα expression may change during disease progression, and conversion of ERα-positive to ERα-negative tumors may occur in approximately 10-20% of patients [164]. Additionally, mutations in ESR1 are described in 20-40% of metastatic cases previously treated with hormone therapy [165,166]. Most of these mutations affect the estrogen-binding domain on the receptor and promote constitutive ERα activity [167].…”
Section: Natural Compounds and Their Effects On Luminal Tumorsmentioning
confidence: 99%